Cucumber CsBPCs Regulate the Expression of CsABI3 during Seed Germination - Mu, Ying; Liu, Yumei; Bai, Longqiang; Li, Shuzhen; He, Chaoxing; Yan, Yan; Yu, Xianchang; Li, Yansu (Frontiers in Plant Science, 2017)
Cucumber seeds with shallow dormancy start to germinate in fruit that are harvested late. ABSCISIC ACID INSENSITIVE3 (ABI3), a transcription factor in the abscisic acid (ABA) signaling pathway, is one of the most important regulators in the transition from late embryogenesis to germination. Our analysis found a candidate cis-regulatory motif for cucumber BASIC PENTACYSTEINE (CsBPC) in the promoter of CsABI3. Yeast one-hybrid and chromatin immunoprecipitation (ChIP) assays showed that CsBPCs bound to the promoter of CsABI3. Examination of β-glucuronidase (GUS) activity driven by the CsABI3 promoter in transgenic Arabidopsis thaliana plants overexpressing CsBPCs and a Nicotiana benthamiana (tobacco) luciferase assay indicated that CsBPCs inhibited the expression of CsABI3. Transgenic plants overexpressing CsBPCs were constructed to confirm that CsBPCs participates in the control of seed germination. This study of the cucumber BPC-ABI3 pathway will help to explore and characterize the molecular mechanisms underlying seed germination and will provide necessary information for seed conservation in agriculture and forestry.